Pengaruh Rekrutmen, Seleksi dan Pengembangan Sumber Daya Manusia terhadap Kinerja Pegawai pada Bank Nagari Cabang Sijunjung - Dewirahmadanirwati, Dewirahmadanirwati; Novelia, Ririn (ARZUSIN, 2025)
This research examines the impact of recruitment, selection, and human resource development on employee performance at Bank Nagari Sijunjung. The study employs a quantitative methodology, utilizing primary data gathered from a total sample of 56 employees through a structured questionnaire. Data processing and analysis were conducted using SPSS version 2021, encompassing validity and reliability tests, classical assumption tests, and multiple regression analysis to evaluate the hypotheses. The findings reveal that recruitment (X1), selection (X2), and human resource development (X3) significantly and positively influence employee performance at Bank Nagari Sijunjung. These results underscore the importance of strategic human resource practices in enhancing employee performance, offering valuable insights for organizational leaders and policymakers aiming to improve workforce effectiveness. The study contributes to the broader literature on human resource management by demonstrating the critical role of recruitment and development processes in driving performance outcomes in banking institutions.